Pepino mosaic virus triple gene block protein 1 (TGBp1) interacts with and increases tomato catalase 1 activity to enhance virus accumulation. (20th June 2013) - Mathioudakis, Matthaios M.; Veiga, Rita S. L.; Canto, Tomas; Medina, Vicente; Mossialos, Dimitris; Makris, Antonios M.; Livieratos, Ioannis
Summary Various plant factors are co‐opted by virus elements (RNA, proteins) and have been shown to act in pathways affecting virus accumulation and plant defence. Here, an interaction between Pepino mosaic virus (PepMV) triple gene block protein 1 (TGBp1; p26) and tomato catalase 1 (CAT1), a crucial enzyme in the decomposition of toxic hydrogen peroxide (H2O2), was identified using the yeast two‐hybrid assay, and confirmed via an in vitro pull‐down assay and bimolecular fluorescent complementation (BiFC) in planta. Each protein was independently localized within loci in the cytoplasm and nuclei, sites at which their interaction had been visualized by BiFC. Following PepMV inoculation, CAT mRNA and protein levels in leaves were unaltered at 0, 3 and 6 days (locally) and 8 days (systemically) post‐inoculation; however, leaf extracts from the last two time points contained increased CAT activity and lower H2O2 levels. Overexpression of PepMV p26 in vitro and in planta conferred the same effect, suggesting an additional involvement of TGBp1 in potexvirus pathogenesis. The accumulation of PepMV genomic and subgenomic RNAs and the expression of viral coat protein in noninoculated (systemic) leaves were reduced significantly in CAT‐silenced plants. It is postulated that, during PepMV infection, a p26–CAT1 interaction increases H2O2 scavenging, thus acting as a negative regulator of plant defence mechanisms to promote PepMV infections.